Algebra Learning Processes Using Scientific Approach and Direct Instruction - Suparman Suparman; Al Jupri (Universitas Sebelas Maret, 2024)
Algebra is one of the mathematical contents which has an essential role in the mathematics field. Nevertheless, most students still find some problems and difficulties in algebra lessons. This study describes the process of algebra learning using the framework of scientific approach and direct instruction. An observational qualitative study involved 71 students and three mathematics teachers from three different public or private senior high schools in West Java, Indonesia. The field notes were used as the instruments. The observational data were analyzed using the framework of the syntaxes of the scientific approach and directed instruction model. Results showed that performing the scientific approach and directed instruction as a learning approach and model in the process of mathematics learning, specifically in algebra learning, should fully pass away all the phases of the learning approach and model. Consequently, by learning algebra contents, such as arithmetic and geometric sequence, matrix determinant, and compound interest, students can optimize some cognitive domains in mathematics, such as communication and conceptual understanding. Particularly, the optimization of questioning activities as the second phase of the scientific approach and demonstrating knowledge and skill as the second phase of the directed instruction model is essential to cultivate and enhance students’ critical thinking in mathematics. The implications to mathematics education are discussed comprehensively